2014
DOI: 10.2337/db13-1234
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Induces Mitochondrial Biogenesis and Glucose Uptake in Subcutaneous Adipose Tissue Through eNOS-Dependent Mechanisms

Abstract: Insulin resistance and obesity are associated with a reduction of mitochondrial content in various tissues of mammals. Moreover, a reduced nitric oxide (NO) bioavailability impairs several cellular functions, including mitochondrial biogenesis and insulin-stimulated glucose uptake, two important mechanisms of body adaptation in response to physical exercise. Although these mechanisms have been thoroughly investigated in skeletal muscle and heart, few studies have focused on the effects of exercise on mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
157
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(174 citation statements)
references
References 49 publications
6
157
0
2
Order By: Relevance
“…[25][26][27] In another study, exercise training by swimming mice for 90 min per day for 30 d resulted in a significant beiging of scWAT as evidenced by increases in Ucp1 and Prdm16. 26 Our work demonstrated that exercise training by voluntary running in a cage containing a wheel for only 11 d resulted in a marked upregulation of numerous beige adipocyte marker genes including Ucp1, Prdm16, Cidea, Elovl3, Pgc1a, Pparg, Cox8b, Dio2, otopetrin, and Tbx1. 21 The wheel cage-trained mice had dramatically increased UCP1 immunofluorescence and the presence of multilocular cells in the scWAT, all of which are consistent with the beiging of scWAT.…”
Section: Effects Of Exercise On Watmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] In another study, exercise training by swimming mice for 90 min per day for 30 d resulted in a significant beiging of scWAT as evidenced by increases in Ucp1 and Prdm16. 26 Our work demonstrated that exercise training by voluntary running in a cage containing a wheel for only 11 d resulted in a marked upregulation of numerous beige adipocyte marker genes including Ucp1, Prdm16, Cidea, Elovl3, Pgc1a, Pparg, Cox8b, Dio2, otopetrin, and Tbx1. 21 The wheel cage-trained mice had dramatically increased UCP1 immunofluorescence and the presence of multilocular cells in the scWAT, all of which are consistent with the beiging of scWAT.…”
Section: Effects Of Exercise On Watmentioning
confidence: 99%
“…[25][26][27] These beige cells were identified by an increase in multilocular adipocytes and an increase in Ucp1, Prdm16 and other markers of BAT or beiging. [25][26][27] In another study, exercise training by swimming mice for 90 min per day for 30 d resulted in a significant beiging of scWAT as evidenced by increases in Ucp1 and Prdm16. 26 Our work demonstrated that exercise training by voluntary running in a cage containing a wheel for only 11 d resulted in a marked upregulation of numerous beige adipocyte marker genes including Ucp1, Prdm16, Cidea, Elovl3, Pgc1a, Pparg, Cox8b, Dio2, otopetrin, and Tbx1.…”
Section: Effects Of Exercise On Watmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise-training, defined as regular bouts of physical activity over a span of weeks, months or years, has well-established effects on adipocyte size (Gollisch et al, 2009;Craig et al, 1981), mitochondrial activity (Stanford et al, 2015a,b;Trevellin et al, 2014;Stallknecht et al, 1991), secretion of adipokines (Golbidi and Laher, 2014;Zachwieja et al, 1997;Bradley et al, 2008;Kraemer et al, 1999;Kanaley et al, 2001) and gene expression (Stanford et al, 2015a,b) in both vWAT and scWAT. There are also specific adaptations to each WAT depot, including adaptations to the structural lipidomic profile changes in scWAT (May et al, 2017) and the beiging of scWAT in rodents (Stanford et al, 2015a,b;Sutherland et al, 2009;Trevellin et al, 2014;Boström et al, 2012;Cao et al, 2011;Stanford and Goodyear, 2016) (Fig.…”
Section: Exercise Effects On Watmentioning
confidence: 99%
“…Beige adipocytes are found intermixed within the WAT and appear morphologically similar to brown adipocytes with multilocular lipid droplets and an abundance of mitochondria (Hirshman et al, 1989;Enerbäck, 2009;Petrovic et al, 2010;Ishibashi and Seale, 2010). In rodents, beige cells can be induced by a variety of stimuli, including β3-selective adrenergic agonists (Ishibashi and Seale, 2010), cold-exposure (Petrovic et al, 2010), exercise (Stanford et al, 2015a,b;Sutherland et al, 2009;Trevellin et al, 2014;Boström et al, 2012;Cao et al, 2011) and an enriched environment (Cao et al, 2011). Upon stimulation, beige adipocytes express very high levels of Ucp1, show increased fuel oxidation and contribute to non-shivering thermogenesis Shabalina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%